A Unique Cytoplasmic–Nuclear Interaction in Sunflower (Helianthus annuus L.) Causing Reduced-Vigor Plants and the Genetics of Vigor Restoration - Liu, Zhao; Gu, Wei; Seiler, Gerald J.; Jan, Chao-Chien (Frontiers in Plant Science, 2020)
Wild Helianthus species are an important genetic resource for sunflower improvement, but sometimes there are adverse interactions between the wild and cultivated cytoplasms. This study reports the inheritance of reduced vigor and its restoration resulting from an interaction of perennial Helianthus cytoplasms with nuclear genes of cultivated sunflower lines. The large number of vigor restoration (V) genes identified in cultivated lines are all located at the same locus, designated V1, suggesting a common origin of these genes. Additional V genes derived from the wild perennial species H. giganteus L. and H. hirsutus Raf. are located at a different locus than V1, designated V2. A major difference between the wild annual Helianthus cytoplasms and perennial cytoplasms is the lack of the vigor-reducing cytoplasms, but surprisingly V genes were observed in wild annual H. annuus L. and H. petiolaris Nutt., which were at the same locus as V1. A common vigor-reducing cytoplasmic effect of the perennial Helianthus species and the existence of a common vigor restoration V gene in most perennial Helianthus species could be explained as a result of vigor selection during Helianthus speciation. V1 was mapped on linkage group (LG) 7 of the sunflower genome, using an F2 population derived from MOL-RV/HA 821. V1 co-segregated with an InDel marker ZVG31, with three SNP markers, SFW01024, SFW07230, and SFW00604, located above it on the map at a genetic distance of 0.8 cM, and another SNP marker, SFW08671, below it at a distance of 0.4 cM. The physical distance between the two closest flanking SNP markers corresponds to 0.56 Mb and 1.37 Mb on the HA 412-HO and XRQ assemblies, respectively. The tightly linked markers will help select normal vigor progenies when using perennial Helianthus cytoplasms in a breeding program, which will also provide a basis for studying the mechanism of the cytoplasmic-nuclear gene interaction, and the speciation of annual and perennial Helianthus species.